Did algal toxin and Klebsiella infections cause the unexplained 2007 mass mortality event in Danish and Swedish marine mammals? - Mollerup, Ida-Marie; Bjørneset, Juni; Krock, Bernd; Jensen, Trine Hammer; Galatius, Anders; Dietz, Rune; Teilmann, Jonas; van den Brand, Judith M.A.; Osterhaus, Albert; Kokotovic, Branko; Lundholm, Nina; Olsen, Morten Tange (The Science of the total environment, 2024)
An unusual mass mortality event (MME) of harbour seals (Phoca vitulina) and harbour porpoises (Phocoena phocoena) occurred in Denmark and Sweden in June 2007. Prior to this incident, the region had experienced two MMEs in harbour seals caused by Phocine Distemper Virus (PDV) in 1988 and 2002. Although epidemiology and symptoms of the 2007 MME resembled PDV, none of the animals examined for PDV tested positive. Thus, it has been speculated that another – yet unknown – pathogen caused the June 2007 MME. To shed new light on the likely cause of death, we combine previously unpublished veterinary examinations of harbour seals with novel analyses of algal toxins and algal monitoring data. All harbour seals subject to pathological examination showed pneumonia, but were negative for PDV, influenza and coronavirus. Histological analyses revealed septicaemia in multiple animals, and six animals tested positive for Klebsiella pneumonia. Furthermore, we detected the algal Dinophysis toxin DTX-1b (1–115 ng g−1) in five seals subject to toxicology, representing the first time DTX-1b has been detected in marine vertebrates. However, no animals tested positive for both Klebsiella and toxins. Thus, while our relatively small sample size prevent firm conclusions on causative agents, we speculate that the unexplained MME may have been caused by a chance incidence of multiple pathogens acting in parallel in June 2007, including Dinophysis toxin and Klebsiella. Our study illustrates the complexity of wildlife MMEs and highlights the need for thorough sampling during and after MMEs, as well as additional research on and monitoring of DTX-1b and other algal toxins in the region. [Display omitted] •An unknown pathogen caused a marine mammal mass mortality event in Scandinavian in 2007.•We reanalysed harbour seal and porpoise samples collected during peak mortalities.•All animals tested negative for virus (PDV, IAV and COVID) and parasites.•Klebsiella pneumonia and the phycotoxin DTX-1b was detected in a subset of seals.•We hypothesize that the 2007 MME was caused by a combination of algal toxin exposure and bacterial infection.